The effect of side chains on the reactive rate and surface wettability of pentablock copolymers by ATRP. Issue 9 (30th November 2013) - Pan, Aizhao; He, Ling; Yang, Shao; Niu, Mingjun
Abstract The reactive rate and surface wettability of three pentablock copolymers PDMS‐b‐(PMMA‐b‐PR)2 (R = 3FMA, 12FMA, and MPS) obtained via ATRP for coatings are discussed. Poly(dimethylsiloxane) (PDMS) is used as difunctional macroinitiator, poly(methyl methacrylate) (PMMA) as the middle block, while poly(trifluoroethyl methacrylate) (P3FMA), poly(dodecafluoroheptyl methacrylate) (P12FMA) and poly(3‐(trimethoxysilyl)propyl methacrylate) (PMPS) as the end block, respectively. Their reactive rates obtained by gas chromatography (GC) analysis indicate that 3FMA gains 8.053 × 10−5 s−1 reactive rate and 75% conversion, higher than 12FMA (4.417 × 10−5 s−1, 35%), but MPS has 1.9389 × 10−4 s−1 reactive rate and 96% conversion. The wettability of pentablock copolymer films is characterized by water contact angles (WCA) and hexadecane contact angles (HCA). The PDMS‐b‐(PMMA‐b‐P12FMA)2 film behaves much higher advancing and receding WAC (120° and 116°) and HCA (60° and 56°) than PDMS‐b‐(PMMA‐b‐P3FMA)2 film (110° and 106° for WAC, 38° and 32° for HAC) because of its fluorine‐rich surface (20.9 wt % F). However, PDMS‐b‐(PMMA‐b‐PMPS)2 film obtains 8° hysteretic contact angle in WAC (114°–106°) and HAC (32°–24°) due to its higher surface roughness (138 nm). Therefore, the fluorine‐rich and higher roughness surface could produce the lower water and oil wettability, but silicon‐rich surface will produce lower water wettability. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40209.